KEBIJAKAN INDONESIA DALAM MENGURANGI EMISI GAS RUMAH KACA BERDASARKAN NATIONALLY DETERMINED CONTRIBUTIONS (NDC PARIS AGREEMENT) - Prisia Asyifa Salma (2022)
Climate change is a global issue that is still hotly discussed and can endanger the earth. The main factor in the occurrence of climate change is human activity which increases over time and the development of the era. With this, many international organizations have tackled climate change issues, for example the United Nations Framework Convention on Climate Change or the UNFCCC. In the UNFCCC, there is a major agreement ratified by almost all countries in the world, namely the Paris Agreement. The Paris Agreement requires all States to give their best efforts through Nationally Determined Contributions or NDCs. As a country that is vulnerable to climate change, Indonesia has also ratified and signed the UNFCCC and the Paris Agreement. Indonesia has set a target for reducing greenhouse gas (GHG) emissions as stated in Indonesia's NDC of 29% (without assistance) and 41% (with international assistance) on a business-as-usual (BAU) basis by 2030. To support Indonesia's NDC, The Indonesian government has issued a Long-Term Strategy for Low Carbon and Climate Resilience or LTS-LCCR. In addition, as one of the ASEAN countries, Indonesia has contributed to the ASEAN Socio-Cultural Community Blueprint 2025 or ASCC Blueprint 2025 by providing 3 proposed activities in the AWGCC Action Plan.